Two Cases With an Early Presented Proopiomelanocortin Deficiency—A Long-Term Follow-Up and Systematic Literature Review - Gregoric, Nadan; Groselj, Urh; Bratina, Natasa; Debeljak, Marusa; Zerjav Tansek, Mojca; Suput Omladic, Jasna; Kovac, Jernej; Battelino, Tadej; Kotnik, Primoz; Avbelj Stefanija, Magdalena (Frontiers in Endocrinology, 2021)
Pro-opiomelanocortin (POMC) deficiency is an extremely rare inherited autosomal recessive disorder characterized by severe obesity, adrenal insufficiency, skin hypopigmentation and red hair. It is caused by pathogenic variants in the POMC gene that codes the pro-opiomelanocortin polypeptide which is cleaved to several peptides, the most notable ones are adrenocorticotropic hormone (ACTH), alpha- and beta-melanocyte-stimulating hormones (α-MSH and β-MSH); the latter two are crucial in melanogenesis and the energy balance by regulating feeding behavior and energy homeostasis through melanocortin receptor 4 (MC4R). The lack of its regulation leads to polyphagia and early onset severe obesity. A novel MC4R agonist, setmelanotide, has shown promising results regarding weight loss in patients with POMC deficiency. A systematic review on previously published clinical and genetic characteristics of patients with POMC deficiency and additional data obtained from two unrelated patients in our care, was performed. A 25-year-old male patient, partly previously reported, was remarkable for childhood developed type 1 diabetes (T1D), transient growth hormone deficiency and delayed puberty. The second case is a girl with an unusual presentation with central hypothyroidism and normal pigmentation of skin and hair. Of all evaluated cases, only 50% of patients had characteristic red hair, fair skin and eyes phenotype. Central hypothyroidism was reported in 36% of patients; furthermore, scarce adolescent data indicate possible growth axis dysbalance and central hypogonadism. T1D was unexpectedly prevalent in POMC deficiency, reported in 14% of patients, which could be an underestimation. POMC deficiency reveals to be a syndrome with several endocrinological abnormalities, some of which may become apparent with time. Apart from timely diagnosis, careful clinical follow-up of patients through childhood and adolescence for possible additional disease manifestations is warranted.